HEALTHY METABOLIC PHENOTYPE IN THE LONG LIFE FAMILY STUDY: WEIGHT GAIN, DISABILITY, AND MORTALITY. (11th November 2018) - Marron, M; Miljkovic, I; Christensen, K; Feitosa, M; Sebastiani, P; Wojczynski, M; Zmuda, J; Newman, A
Abstract: The Long Life Family Study (LLFS) is a multi-center cohort of two-generation families selected for longevity. LLFS families with healthy metabolism may indicate unique factors influencing longevity. We developed a novel healthy metabolic phenotype, hypothesizing it would be associated with less weight gain and lower incident disability and mortality. The healthy metabolic phenotype was developed in the offspring generation by applying a Latent Profile Analysis to age- and gender-adjusted z-scores of body mass index, waist circumference, interleukin-6, C-reactive protein, and fasting glucose, insulin, triglycerides, and high-density lipoprotein cholesterol. Offspring met the individual-level healthy metabolic phenotype if classified into the latent subgroup with a profile of healthier metabolic markers than expected given age and gender. Families met the healthy metabolic phenotype if ≥2 and ≥50% of their offspring met the individual-level healthy metabolic phenotype. Among 1987 offspring (43% men; mean age: 60 ± 8), 388 (20%) met the individual-level healthy metabolic phenotype (heritability=0.40, p=2.15X10-27). Consistent with our phenotype (which includes body mass index), these offspring had a 10kg lower average weight at age 50. Offspring with the healthy metabolic phenotype also had an average weight gain from age 50 to baseline of only 0.01kg/year versus 0.36kg/year among remaining offspring. Among 388 families, 39 (10%) met the healthy metabolic phenotype. Adjusting for age and gender, proband-generation participants (45% men; mean age=90 ± 6) from families with the healthy metabolic phenotype had 28% (95% CI=0.52–0.99) and 39% (0.47–0.80) lower risks of incident disability and mortality, respectively. These findings further validate the importance of a healthy metabolic phenotype.